(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article explores various methods for fostering creative thinking in primary school students, emphasizing the importance of creativity in modern education. Creative thinking, defined as the ability to generate original ideas and solve problems in innovative ways, is crucial for developing critical thinking, flexibility, and resilience in young learners. The paper discusses several key teaching strategies, including inquiry-based learning, project-based learning, arts integration, and the use of problem-solving activities. Additionally, the role of teachers in cultivating a supportive, risk-free environment and the impact of technology on creativity are examined. Despite challenges such as standardized testing, the paper argues for the essential role of creativity in preparing students for future success